Effect of Incubation Time on Amylase Enzyme Activity in Cassava Tape - Yurnaliza (International Journal of Ecophysiology, 2022)
Cassava tape is a product made by a fermentation process that requires the help of microorganisms. The tape fermentation process involves the enzyme amylase. Amylase is a glycoside hydrolase enzyme that catalyzes the breakdown of starch into simple sugars. Enzyme activity can be calculated by measuring the amount of product formed, or by calculating the amount of substrate reduction in a given unit of time. This study aims to determine the effect of incubation time on amylase enzyme activity in cassava tape. The research method used was the descriptive experimental method. The results of the experiment showed a reduction in the substrate due to amylase enzyme activity. The highest percentage of substrate reduction occurred at 48 hours incubation time and the lowest percentage at 144 hours incubation time. An organoleptic test was conducted with color, aroma, texture, and taste parameters conducted on 30 panelists. Incubation time affected the percentage of substrate reduction and organoleptic parameters